1967
DOI: 10.1111/j.1365-2044.1967.tb02725.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on intragastric pressure

Abstract: Regurgitation of stomach contents, as distinct from vomiting, is the result of a sufficiently high intragastric pressure overcoming the competence of the cardia.In the last fifteen years there have been several studies designed to demonstrate the nature of the cardiac sphincter and to evaluate the pressure required to cause retrograde flow through it13zp 3,4. By contrast, there has been much less consideration given to values for intragastric pressure.Our interest in this matter stemmed from anxiety for the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 10 publications
1
16
0
3
Order By: Relevance
“…It has been proposed that increased abdominal pressure by the enlarged uterus may contribute to the occurrence of reflux during pregnancy. However, the findings in the literature are conflicting [30,31]. Given that regurgitation is frequent in pregnancy (74% in our sample), further studies are needed to investigate this condition.…”
Section: Discussionmentioning
confidence: 57%
“…It has been proposed that increased abdominal pressure by the enlarged uterus may contribute to the occurrence of reflux during pregnancy. However, the findings in the literature are conflicting [30,31]. Given that regurgitation is frequent in pregnancy (74% in our sample), further studies are needed to investigate this condition.…”
Section: Discussionmentioning
confidence: 57%
“…The application of cricoid force results in a fall in lower oesophageal sphincter tone, whereas suxamethonium-induced fasciculations produce a rise in mean intragastric pressure. 20,[25][26][27] Previous research has demonstrated that accurately applied cricoid force in excess of 30 N occluded the upper oesophagus, creating an effective barrier to regurgitation and aspiration. [14][15][16] Although Wraight et al extrapolated from their research that a force of 44 N would prove protective in situations of elevated intragastric pressure, most commentators recommend 30-40 N as the target range.…”
Section: No Participantsmentioning
confidence: 99%
“…Can we apply less force and still prevent regurgitation? In practice it would seem that gastric pressures are generally < 25 mmHg in the supine position under general anaesthesia [14,15], even during emergency Caesarean section with a full stomach [16]. Therefore 30 N of force is probably more than enough to prevent regurgitation [11].…”
Section: Discussionmentioning
confidence: 99%